The legislative process - Walker, Harvey; Heitshusen, Valerie; Oleszek, Walter J.; Library of Congress (Washington, D.C. : Library of Congress, 2013)
An introduction to the Congressional legislative process. Includes video and transcripts of narrated text.
Description based on contents viewed on May 1, 2013; title from home page.
Keywords: United States. -- Congress -- Rules and practice; United States. -- Congress; Legislation -- United States; Bill drafting -- United States; Legislative calendars -- United States; Bill drafting; Legislation; Legislative calendars; United States; Rules